Selective synthesis of N,N-dimethyl aniline derivatives using dimethyl carbonate as a methylating agent and onium salt as a catalyst - Shivarkar, A. B.; Gupte, S. P.; Chaudhari, Raghunath V. (Journal of Molecular Catalysis A - Chemical, 2005)
N-Alkylation of anilines by dimethyl carbonate (DMC) catalyzed by onium salts has been demonstrated. The work presented here shows that a simple catalytic system consisting of onium salts in the presence of a small amount of water is extremely effective in enhancing the DMC mediated N-alkylation of anilines to dialkylated products. The effect of reaction conditions on the synthesis of N,N-dimethyl aniline (NNDMA) from aniline and DMC has been investigated. Under the optimized conditions highest yield of NNDMA obtained was 99.8%, which is the best reported for liquid phase N-alkylation of aniline using DMC. The role of water in enhancing the yield of NNDMA is explained and a reaction-networking scheme is constructed, which summarizes the chemistry behind liquid phase N-alkylation of anilines by DMC. The catalyst has been shown to recycle up to five times and at the end of fifth recycle almost 98% of NNDMA yields were obtained. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: Aniline; Dimethyl carbonate; methylation; N; N-alkylation; N-dimethyl aniline; onium salts